The Paradiplomatic Role of the ConIFA in Promoting Self-Determination of Marginalised Entities - Ario Bimo Utomo (Global Strategis, 2019)
The purpose of this paper is to apply the paradiplomacy framework in exploring the role of NGOs in promoting the issue of marginalised peoples. More specifically, it highlights the Confederation of Independent Football Association (ConIFA), an international football governing body comprising minority peoples, stateless nations, and regions which are unrecognised by the Federation Internationale de Football Association (FIFA). The author attempts to discuss ConIFA’s ability in voicing the issue of self-determination concerning its members, which are mainly sidelined in the mainstream international affairs. This paper discusses two questions: (1) does ConIFA qualify to be regarded as a paradiplomatic actor? If yes, in what ways? and (2) to what extent does ConIFA advocate the issue of self-determination of its members? In so doing, the researcher first studies the nature of ConIFA through its own constitution as well as examining its activities through various sources. Second, the author also utilises core concepts on paradiplomacy to seek in which category does ConIFA’s activities fall into. The findings suggest that ConIFA qualifies as a paradiplomatic actor in the sense that it has two forces: horizontal and vertical. Horizontally, it platforms its members to interact with like-minded counterparts through numerous activities. Vertically, ConIFA also possesses a comparative advantage to reach a wider audience by framing the issue through sport. However, the study also indicates that while self-determination is promoted through ConIFA, the organisation does not possess enough political capacity to facilitate a deeper advocacy, thus making its paradiplomatic activities mainly fall into the cultural category.